(untitled) (Agricultural Engineering, 2019)
Paper presents research concerned utilization of natural gas in a liquid state as a new source of electrical energy generation in country side areas of Russia to use it in a small family farms and bigger agriculture enterprises. The experiment shows that alcohol and gasoline are more expensive products to be a source for electricity generation as a reserve energy supply in agriculture production areas of the country. Introduction of natural gas generator as an alternative fuel makes possible to produce low cost of electrical energy in any part of the country, what gives great potential to alternative energy supply, but especially for agriculture production on small households and also bigger enterprises.